2013
DOI: 10.1103/physrevlett.111.157002
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of a Superhard Iron Tetraboride Superconductor

Abstract: Single crystals of novel orthorhombic (space group Pnnm) iron tetraboride FeB4 were synthesized at pressures above 8 GPa and high temperatures. Magnetic susceptibility and heat capacity measurements demonstrate bulk superconductivity below 2.9 K. The putative isotope effect on the superconducting critical temperature and the analysis of specific heat data indicate that the superconductivity in FeB4 is likely phonon mediated, which is rare for Fe-based superconductors. The discovered iron tetraboride is highly … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
200
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 208 publications
(214 citation statements)
references
References 35 publications
13
200
0
1
Order By: Relevance
“…However, after an exhausting search of the known structures for TMB x , the orthorhombic TMB 4 (TM = Cr, Mn, and Fe) is found to exhibit a 3D bonding network between TM and boron [15,17,27], which is structurally more favorable than hexagonal TMB 4 for producing mechanically isotropic borides. As expected, recent reports show that the orthorhombic FeB 4 and MnB 4 possess a superior nanoindentation hardness of 62 GPa and a Vickers hardness of H V = 37.4 GPa under a load of 9.8 g [13,14], approaching the superhard regime as defined by the asymptotic H V ≥ 40 GPa. Strikingly, both borides also exhibit intriguing superconducting and magnetic properties [13,14,16] .…”
Section: Introductionmentioning
confidence: 67%
See 2 more Smart Citations
“…However, after an exhausting search of the known structures for TMB x , the orthorhombic TMB 4 (TM = Cr, Mn, and Fe) is found to exhibit a 3D bonding network between TM and boron [15,17,27], which is structurally more favorable than hexagonal TMB 4 for producing mechanically isotropic borides. As expected, recent reports show that the orthorhombic FeB 4 and MnB 4 possess a superior nanoindentation hardness of 62 GPa and a Vickers hardness of H V = 37.4 GPa under a load of 9.8 g [13,14], approaching the superhard regime as defined by the asymptotic H V ≥ 40 GPa. Strikingly, both borides also exhibit intriguing superconducting and magnetic properties [13,14,16] .…”
Section: Introductionmentioning
confidence: 67%
“…As expected, recent reports show that the orthorhombic FeB 4 and MnB 4 possess a superior nanoindentation hardness of 62 GPa and a Vickers hardness of H V = 37.4 GPa under a load of 9.8 g [13,14], approaching the superhard regime as defined by the asymptotic H V ≥ 40 GPa. Strikingly, both borides also exhibit intriguing superconducting and magnetic properties [13,14,16] .…”
Section: Introductionmentioning
confidence: 67%
See 1 more Smart Citation
“…Recently, Gou et al have reported that FeB 4 in the oP10 ground state has been synthesized at pressures above 8 GPa and high temperature up to 2000 K. 7 The superconductivity at 3 K was verified by diamagnetism and the isotope effect, but the sample was too small for measuring the resistive transition. Given the small fraction of the volume which was found to exhibit superconducting behavior in our samples, there may also be a small fraction of superconducting oP10 FeB 4 in our film.…”
Section: T © 2013 Author(s) All Article Content Except Where Othermentioning
confidence: 99%
“…To get around this problem, one can synthesize bulk compounds under high pressure. 7 Another synthesis route is to make use of non-equilibrium thin film processes such as pulsed laser deposition and magnetron sputtering. In this study, we have utilized thin film co-sputtering composition spreads to search for possible superconducting phases in the Fe-B binary system.…”
Section: T © 2013 Author(s) All Article Content Except Where Othermentioning
confidence: 99%